Pendampingan Posyandu Remaja Puskesmas dalam Mensosialisasikan Bahaya Pernikahan Dini di SMA Negeri 1 Ambarawa Pringsewu - Istiani, Ade Nur; Aisyah, Umi; Amalia, Fiqih; Rogamelia, Risna (Civitas Consecratio: Journal of Community Service and Empowerment, 2024)
Early marriage is a marriage entered into by a minor before the age of 19 years. Even though there is a marriage law that regulates the age of marriage, in society this phenomenon is something that is normal and commonly practiced. Even though early marriage has a positive side, the negative side is much greater, namely the loss of children’s rights such as the right to education, the right to health, the right to protection from exploitation and so on. Puskesmas is one of the health institutions that has a youth posyandu program. Youth Posyandu is a health-based activity specifically intended for teenagers. This activity will discuss physical and mental health with the aim of helping adolescent development. One of the focuses of this activity is to provide outreach to teenagers about reproductive health. Because today’s teenagers are involved in promiscuity and end up getting married underage. However, in the community health center there is still a lack of youth posyandu cadres and the majority of these activities are carried out on teenagers or students who have had early marriages and there are no preventive or prevention activities. Therefore, the service team feels it is important to help youth posyandu disseminate material about the dangers of early marriage and motivate them. to focus more on preparing for a better future.